Clarissa Harlowe; or the history of a young lady $1 (BVolume 2s - Richardson, Samuel, 1689-1761 (Salt Lake City, UT : Project Gutenberg, 2006)
"Clarissa Harlowe; or the History of a Young Lady $1 (BVolume 2" by Samuel Richardson is a novel written during the early 18th century. This epistolary work delves into the complex emotions and societal expectations surrounding the titular character, Clarissa Harlowe, as she navigates familial pressures, romantic pursuits, and her quest for autonomy in a patriarchal society. The narrative explores themes of love, obligation, and the struggle for personal freedom. The opening of this volume introduces letters exchanged between Clarissa and her confidante Miss Howe, where Clarissa grapples with increasing familial hostility and the prospect of being coerced into marrying Mr. Solmes$1 (Bwhom she despises. Various characters, including her brother and sister, exert pressure on her, revealing their disdain for her spirited independence. Clarissa passionately expresses her reluctance to comply with her family's wishes while detailing her emotional turmoil and longing for a sense of agency. The letters set the tone for a turbulent confrontation between personal desire and societal expectation, piquing the reader's curiosity about the outcomes of Clarissa's struggle against her oppressive circumstances. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Clarissa
Release date is 2006-01-01
Produced by Julie C. Sparks, and David Widger
Keywords: England -- Fiction; Psychological fiction; Epistolary fiction; Conflict of generations -- Fiction; Kidnapping victims -- Fiction; Young women -- Crimes against -- Fiction; Rape victims -- Fiction